The complete chloroplast genome of Codonopsis lanceolata (Campanulaceae) - Lee, Junki (Mitochondrial DNA B Resour, 2018)
The complete chloroplast genome sequence of Codonopsis lanceolata was determined by next generation sequencing. The total length of chloroplast genome of C. lanceolata was 169,447 bp long, including a large single-copy (LSC) region of 85,253 bp, a small single-copy (SSC) region of 8060 bp, and a pair of identical inverted repeat regions (IRs) of 38,067 bp. A total of 110 genes was annotated, resulting in 79 protein-coding genes, 27 tRNA genes, and 4 rRNA genes. The phylogenetic analysis of C. lanceolata with related chloroplast genome sequences in this study provided the taxonomical relationship of C. lanceolata in the genus Campanula.